(untitled) (Global Scientific Review, 2024)
The development of novel membranes capable of efficiently and accurately separating oil and water is essential for effective oily wastewater treatment. In this study, we successfully fabricated a superhydrophilic stainless steel mesh membrane (SSM) by incorporating flower-like TiO2 nanosheets (TiO2-FLn) onto its surface via a hydrothermal process. The unique nanostructure of TiO2-FLn imparts exceptional superhydrophilicity and underwater superoleophobicity to the SSM, enabling efficient oil-water separation. The SSM/TiO2-FLn membrane demonstrates outstanding performance, exhibiting a separation efficiency of 98%, an ultrahigh flux of 75,228 L/m²·h, remarkable recyclability, and long-term durability. Furthermore, the SSM/TiO2-FLn membrane maintained a separation efficiency consistently above 94% even after 15 cycles. Additionally, it exhibited exceptional thermal and chemical stability under various conditions, including different pH ranges and NaCl concentrations. The successful fabrication of this innovative membrane holds significant promise for advancing oily wastewater treatment practices.